'It can never be as perfect as home': An explorative study into the fostering experiences of unaccompanied refugee children, their foster carers and social workers. (May 2020) - Rip, Jet; Zijlstra, Elianne; Post, Wendy; Kalverboer, Margrite; Knorth, Erik J.
Highlights: Unaccompanied child, carers, social workers in general satisfied with foster placement. Cultural similarity in foster placement valued; similarity in language valued most. Some children reported negative experiences but still rated placement as successful. Several children did not feel at home in foster placement. Less appreciation of cultural similarity by former unaccompanied children. Abstract: Research shows that highly supportive living arrangements, such as foster care, can provide an environment that meets the needs of unaccompanied children (i.e. fewer internalizing problems, higher quality of the child-rearing environment). However, there is limited research into the experiences of these children in (cultural) foster care. The aim of this study is to explore the experiences of former unaccompanied refugee children and unaccompanied refugee children, their carers and social workers with regard to the foster placement. This cross-sectional qualitative study combined semi-structured interviews with questionnaires. In general, participants were satisfied with the foster placement. However, some children also reported negative experiences during their foster placement or felt somewhat uncomfortable, but they still rated the placement as successful. Children and carers valued the cultural similarity of the foster placement. Former unaccompanied children appreciated cultural similarity less. Overall, participants valued similarity of language the most. Several children did not feel at home in their foster placement. In most foster families, the caregiving environment offered to children seemed adequate.